Moderasi Bermazhab dalam Pandangan Lembaga Dakwah Mahasiswa UIN Alauddin Makassar - Muh Munandar; M. Thahir Maloko (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
The background raised in this study is the development of many intolerant acts which are the fruit of the doctrines of the schools developed by various schools and this has hit various regions including the educational institution of UIN Alauddin Makassar, this can then be countered by spreading the notion of the concept of moderation. The formulation of the problems raised are: 1) What are the indicators of the concept of moderation? 2) What is the concept of mazhab moderation in the view of campus da'wah institutions? 3) What is the goal of developing the concept of mazhab moderation according to campus da'wah institutions?. This type of research is a social research with a qualitative descriptive format, the research location is at UIN Alauddin Makassar, the research approach used is a case study. The data sources used are primary data sources in the form of direct interviews and secondary data sources, namely through journals, books and other scientific literature. The method of data collection was carried out through a process of observation, interviews and documentation using structured and measurable research instruments. The data analysis method is through the stages: 1) data reduction, 2) data display, 3) verification and drawing conclusions. The results show that 1) The indicators of the concept of moderation are aspects of divinity, prophethood, balance, belief in the last days and justice in society, 2) The growth of the concept of moderation has been understood and carried out quite well by several leaders and activists of campus da'wah institutions by conducting systematic studies both directly or indirectly and is also carried out by tracing the roots of the differences between the concept of moderation and other concepts, 3) The purpose of the concept of moderation itself is to create an attitude of mutual respect and respect for other people, both from different schools of thought and even different beliefs while maintaining the principles as an indicator of the concept of moderation itself.